Application of Hungarian Assignment Method On Distribution Task Area SPG using Visual Basic 6.0 - Astri Fatma Sari; Hj. Latifah Hj. Latifah, SSi,MMSI (Jurnal Sistem Informasi, 2008)
This application seeks maximum profits in a company,using the Assignment problem,Hungarian method, maximization problem on Operational Research Techniques. In thismatter as assign the SPG (Sales Promotion Girls) and as a Regional Task Assignment(counter). These applications include data acquisition benefits every SPG in each counterboutique then calculated per group using the method Hungarian optimal results that will showprofits zoning tasks each SPG.Bibliography: 5 books (1988 to 2007)Keywords: Assignment, Hungarian, maximization (X + 67 + Annex)